The homage to Major Thulin (Fiep Bulletin - online, 2015)
On his eightieth birthday Major Thulin was congratulated by gymnastic teachers and gymnasts all over the world. But while governments, societies, and private persons abroad were thanking him for his contributions to the development and organization of modern gymnastics and organization.